Accumulation factor of heavy metals in capoeta umbla fish species - Canpolat, Özgür (My University, 2013)
In this study, some heavy metal concentrations (copper, iron, zinc, cobalt, cadmium, chromium, lead and arsenic) were determined in water and in muscle of Capoeta umbla fish to study the potential human risk of consumption and the relationship between the heavy metal load of fish and some of their biological aspects (weight, length and sex). In addition, the accumulation factors of heavy metals in Capoeta umbla were determined. Water and fish samples were analysed using ICP to determine concentrations of Cu, Fe, Zn, Co, Cd, Cr, Pb and As. It was found that heavy metals were accumulated in muscles of C. umbla in concentrations higher than that in the water. The correlations between the heavy metal concentrations of fish samples have opposite trends to those of sizes of fish. The metal levels in the muscles of females were higher than those in males. All accumulation factors (AF) for water were >1.00 which means that the C. umbla accumulated metals from water. The results were discussed and compared with tolerable values for heavy metals provided from the EPA and FAO to determine whether this species has any risk for human consumption. © by PSP.
Keywords: Accumulation factor; Capoeta umbla; Heavy metals; Muscle; Turkey; Water